2002
DOI: 10.1152/ajpheart.00682.2001
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia in the thymus: role of oxygen tension in thymocyte survival

Abstract: in the thymus: role of oxygen tension in thymocyte survival. Am J Physiol Heart Circ Physiol 282: H1467-H1477, 2002. First published January 3, 2002 10.1152/ajpheart.00682.2001.-Our previous studies using oxygen microelectrodes showed that the thymus is grossly hypoxic under normal physiological conditions. We now have investigated how oxygen tension affects the thymus at the cellular and molecular level. Adducts of the hypoxia marker drug pimonidazole accumulated in foci within the cortex and medulla and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 33 publications
(47 reference statements)
5
51
0
9
Order By: Relevance
“…5) and widespread staining with the PIM hypoxia marker (SI Fig. 8B) consistent with the previous study of Hale et al (25). The intensity of staining with the anti-PIM antibody was met only by bone marrow cells isolated from the SP ''tip'' region (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…5) and widespread staining with the PIM hypoxia marker (SI Fig. 8B) consistent with the previous study of Hale et al (25). The intensity of staining with the anti-PIM antibody was met only by bone marrow cells isolated from the SP ''tip'' region (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…8B). These results confirm the overall hypoxic state of thymic tissue as shown previously (25). In the bone marrow fractions, non-SP cells demonstrated only a small shift of PIM staining as compared with the saline control mice (R1 region in Fig.…”
Section: Distribution Of Different Hematopoietic Subsets Along a Ho Dyesupporting
confidence: 91%
See 1 more Smart Citation
“…The stem cells are prone to use anaerobic metabolism, perhaps as a means to reduce genotoxic stress associated with reactive oxygen species generated from aerobic metabolism 18 . Oxygen electrode and hypoxia marker drug studies have demonstrated that the thymus of mice is heterogeneously hypoxic 6,15 , but in this tissue there is no evidence for HIF1-regulated gene expression 15 . Recently it was shown that lymphocyte motility in lymph nodes is affected by pO 2 , with motility decreasing with oxygen content 26 .…”
Section: Regulation Of Hif1 By Hypoxiamentioning
confidence: 98%
“…Examples of relatively hypoxic normal tissues include pericentral vein cells in the liver 12 , portions of the retina (in the dark) 13 , spinous layer of the epidermis 14 , the thymus 6,15 , renal tubular epithelium 16 , myocardium (particularly during exercise) 17 and subregions of the bone marrow that are enriched for stem cells 18 . Hypoxia has diverse roles in the function of these normal tissues.…”
Section: Regulation Of Hif1 By Hypoxiamentioning
confidence: 99%